Analisis Yuridis Terhadap Mitigasi Risiko Penyaluran DAU/DBH pada HIMBARA - M Rivky Abdillah Putra; Annisa Sativa (Universitas Cokroaminoto Yogyakarta, 2027)
This normative-juridical study aims to analyze the mechanism for distributing the General Allocation Fund (DAU) and Revenue-Sharing Fund (DBH) through the Association of State-Owned Banks (HIMBARA) to